Shape resonance in electron molecule scattering using coupled cluster method - Pal, Sourav; Vaval, Nayana; Sajeev, Y. (Indian Journal of Physics and Proceedings of the Indian Association for the Cultivation of Science, 2007)
The Fock space multi-reference coupled-cluster (FSMRCC) method along with the complex absorbing potential (CAP) is used for the study of the shape resonance energy and width in an electron molecule collision. We study the shape resonances in e(-) -H2CO and e(-) -CO.
Keywords: electron-molecule scattering; multi-reference coupled-cluster